2009
DOI: 10.1029/2009jg000951
|View full text |Cite
|
Sign up to set email alerts
|

Energy, water, and carbon fluxes in a loblolly pine stand: Results from uniform and gappy canopy models with comparisons to eddy flux data

Abstract: [1] This study investigates the impacts of canopy structure specification on modeling net radiation (R n ), latent heat flux (LE) and net photosynthesis (A n ) by coupling two contrasting radiation transfer models with a two-leaf photosynthesis model for a maturing loblolly pine stand near Durham, North Carolina, USA. The first radiation transfer model is based on a uniform canopy representation (UCR) that assumes leaves are randomly distributed within the canopy, and the second radiation transfer model is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 84 publications
(120 reference statements)
0
31
0
Order By: Relevance
“…Tree crown size is not only a critical canopy structural parameter for understanding forest ecosystem function (Song et al, 2009), but it is also significantly related to DBH, the major structural parameter that is often used to infer numerous other structural parameters (Gholz et al, 1979;Grier & Logan, 1977;Jenkins et al, 2004). Table 1 shows that there is a significant allometric relationships between CD and DBH on a species-specific basis.…”
Section: Potential In Estimating Other Canopy Structure Variablesmentioning
confidence: 97%
See 2 more Smart Citations
“…Tree crown size is not only a critical canopy structural parameter for understanding forest ecosystem function (Song et al, 2009), but it is also significantly related to DBH, the major structural parameter that is often used to infer numerous other structural parameters (Gholz et al, 1979;Grier & Logan, 1977;Jenkins et al, 2004). Table 1 shows that there is a significant allometric relationships between CD and DBH on a species-specific basis.…”
Section: Potential In Estimating Other Canopy Structure Variablesmentioning
confidence: 97%
“…Consideration of between-crown gaps is a major step toward more realistic characterizations of forest canopies from the traditional turbid medium representation where leaves are assumed to be randomly distributed in the entire canopy space without crown boundaries. Song et al (2009) found that a uniform canopy representation can lead to overestimation of radiation interception, transpiration, and carbon assimilation in the canopy. Therefore, tree crown size is essential for more accurate understanding of ecosystem function.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Stomata control the amount of water transpired by vegetation so that stomatal conductance and its scaling from leaf to canopy are key processes in estimating ET. Following approaches developed for global climate models (GCMs) [ Dai et al ., ; Cox et al ., ; Bonan et al ., ; Clark et al ., ; Kowalczyk et al ., ; Oleson et al ., ] and ecosystem productivity models [ Campbell and Norman , ; Medlyn et al ., ; Song et al ., ; Evers et al ., ; Baker et al ., ], we implemented a coupled photosynthesis‐based stomatal conductance model with sunlit and shaded leaves in the PX LSM for coupling ET estimation with CO 2 assimilation.…”
Section: Photosynthesis‐based Stomatal Conductance Approachmentioning
confidence: 99%
“…Recent efforts have been made to develop and evaluate a simplified GORT model for the use in coupled global dynamic terrestrial ecosystem models Yang et al, 2010). Despite these successful applications, the current version of the GORT model does not have analytical solutions for radiation absorption by sunlit and shaded leaves, though previous studies have tried to solve the process of multiple scattering between canopy and background in an iterative manner (Song et al, 2009). However, sunlit and shaded leaves must be treated separately in photosynthesis modeling because flux densities of photosynthetically active radiation (PAR) incident on leaf surfaces are different (He et al, 2013).…”
Section: Q Xin Et Al: Modeling Photosynthesis Of Discontinuous Planmentioning
confidence: 99%